2016
DOI: 10.1192/bjpo.bp.116.002816
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary survey on the religious profile of Brazilian psychiatrists and their approach to patients' religiosity in clinical practice

Abstract: BackgroundAlthough there is evidence of a relationship between religion/spirituality and mental health, it remains unclear how Brazilian psychiatrists deal with the religion/spirituality of their patients.AimsTo explore whether Brazilian psychiatrists enquire about religion/spirituality in their practice and whether their own beliefs influence their work.MethodFour hundred and eighty-four Brazilian psychiatrists completed a cross-sectional survey on religion/spirituality and clinical practice.ResultsMost psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 30 publications
2
20
0
5
Order By: Relevance
“…However, caution is recommended when using these treatments, as this is a private and personal matter that should be considered but not used as a prescription [ 68 ]. In addition, some doctors do not feel prepared to integrate R/S in clinical practice [ 69 71 ]. These observations endorse the necessity of introducing the R/S topic into medical schools to clarify the clinical implications and professional conduct in the field [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, caution is recommended when using these treatments, as this is a private and personal matter that should be considered but not used as a prescription [ 68 ]. In addition, some doctors do not feel prepared to integrate R/S in clinical practice [ 69 71 ]. These observations endorse the necessity of introducing the R/S topic into medical schools to clarify the clinical implications and professional conduct in the field [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 Surveys of mental health professionals have indicated the main reasons why R/S has not been routinely addressed in clinical practice, with a lack of training being among the most frequently cited. 10,11 Surveys have found that mental health professionals tend to be less religious than their patients, constituting what has been called a ''religiosity gap.'' [11][12][13] This lower religiosity among mental health professionals seems to be at least partially related to some anti-R/S bias and a pathologizing of R/S in professional training, especially among those whose training was less recent.…”
Section: Introductionmentioning
confidence: 99%
“…However, many health professionals still find it difficult to address the issue of patients' R/S (38) . Therefore, several publications have addressed how to integrate R/S in an ethical and responsible way, based on scientific evidence, in clinical care (36,39) .…”
Section: Discussionmentioning
confidence: 99%